Synthesis and Characterization of Nanoparticle Calcium Oxide (CaO) from Blood Calm Shell by Precipitation Methods - Aisy Aulia Amri; Zahranisa Shorea; Caecilia Puji Astuti (Advance Sustainable Science Engineering and Technology, 2024)
Blood Clam (Anadara granosa) contains high calcium carbonate which can be utilized in various fields by being used as nanotechnology. The shell contains 98.7% CaCO3 making it a sustainable material source. The research aims to synthesize and characterize of calcium oxide nanoparticles by precipitation methods. This method begins with crushing the shell into 100 mesh as sample. Each sample is mixed with HCl solute. After mixing, each filtrate is precipitated with KOH solute to multiple pH (7 ; 9 ; 11). The method continues with neutralizing the precipitate with water until it reach pH 7 and drying it with oven in 100oC for 1 hour. The sample will be calcinated for 3 hours in various temperature (300oC ; 500oC ; 900oC). Samples will be analyzed with SEM-EDX and XRF Analysis. Research indicates that The degree of acidity and calcination temperature do not have a significant effect on calcium oxide content. The calcium oxide content is ranged between 82,58% - 87,47% with the sizes being ranged between 550 nm - 20mm.